Pengujian Bahan Formulasi MsNPV ( Mythimna separata Nuclear Polyhedrosis Virus) terhadap Ulat Grayak Padi, Mythimna separata Walker di Lapangan - Trisnaningsih Trisnaningsih; Arifin Kartohardjono (Perhimpunan Entomologi Indonesia, 2009)
The objective of these studies were to observe efficiency material formulations of MsNPV and the influence to rice plantation on different locations (Indramayu (3 m above sea level), Sukabumi (400m above sea level) and Bogor (250 m above sea level) to larvae of rice army worm. This study used randomized block design with 4 treatments consisted of 3 formulation materials (talc, kaolin and gypsum) and control in five replications. Observations were done to life and death larvae on 5, 10, 15 days after inoculation and leaf damaged. Data were analysed with DMRT. Results from this study indicated that material talc formulation was more effective because all the material was dissolve as compare to material kaolin and gypsum formulations while the material were precipitated. Utilize these three material formulations on three different locations above sea level gave the same impact to the mortality army worm larvae and also to the plant damage.